Does Beta Move with News? Firm-Specific Information Flows and Learning about Profitability - Patton, Andrew J.; Verardo, Michela (Review of Financial Studies, 2012)
We investigate whether stock betas vary with the release of firm-specific news. Using daily firm-level betas estimated from intraday prices, we find that betas increase on earnings announcement days and revert to their average levels two to five days later. The increase in betas is greater for earnings announcements that have larger positive or negative surprises, convey more information about other firms in the market, and resolve greater ex ante uncertainty. Our results are consistent with a learning model in which investors use information on announcing firms to revise their expectations about the profitability of the aggregate economy. The Author 2012. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.